Local-free recurrence survival after breast-conserving surgery and the breast cancer complex treatment - A. D. Zikiryahodjaev; M. V. Ermoshchenkova; A. R. Bosieva; J. F. Omarova; N. N. Volchenko; I. V. Reshetov (Сеченовский вестник, 2021)
Aim. To determine the frequency of local recurrence of breast cancer (BC) after performing breast-conserving surgery (BCS) during and after complex treatment, to study the risk factors for local recurrence and survival.Materials and methods. A retrospective cohort study of 675 patients with breast cancer who underwent BCS followed by remote radiotherapy was conducted. The frequency of local relapse and risk factors were studied, 3- and 5-year local-free survival. The odds ratios (OR) and 95% confidence intervals (CI) were calculated, and the Kaplan–Meyer curves were constructed.Results. Radical breast resections (RBR) were performed in 46.7% of patients, and oncoplastic breast resections (OBS) in 53.3% of patients. The most common histological type in both groups was invasive cancer with no signs of specificity: 76.9% and 84.1% – in the OBS and RBR groups, respectively. The incidence of cancer in situ was higher in the OBS group: 14.7% vs. 3.3% in the RBR group (p < 0.001), metastases in regional lymph nodes were more frequent in the RBR group: 34.3% against 20.3% in OBS (p < 0.001). According to the immunohistochemical type and degree of differentiation, the groups did not differ. For 3 years, the relapse-free survival rate was 99.7% in both groups, and for 5 years – 99.2% in the OBS group. and 99.7% in the RBR group, 6 years – 98.3% and 98.7%, respectively; no significant differences were found between the groups. There were no statistically significant differences in the frequency of relapses depending on the width of the resection edges from <1 to ≥10 mm. The risk of relapse was increased with a preserved menstrual status (OR 20.05; 95% CI 2.52–159.33), Her2/neu–positive (OR 5.11; 95% CI 1.04–25.09) and triple-negative types (OR 4.02; 95% CI 1.02–15.95), the degree of differentiation of G3 (OR 5.58; 95% CI 1.59–19.64).Conclusion. BCS is characterized by oncological safety; the rate of local relapse within 6 years is 1.5%. Risk factors for relapse include active menstrual status, highly aggressive immunohistochemical types of breast cancer, and low degree of differentiation.